Quantification of ammonia in human breath by the selected ion flow tube analytical method using H30+ and 02+ precursor ions - Spanĕl, P; Davies, S; Smith, D (Rapid communications in mass spectrometry, 1998)
We show how our selected ion flow tube mass spectrometric technique for trace gas analysis can be used to determine the concentrations of ammonia in alveolar breath from single exhalations using both H30+ and 02+ precursor ions for chemical ionization. Thus, data are presented of the alveolar ammonia concentrations in the breath of six healthy volunteers following the ingestion of a liquid protein meal, which show that consistent values are obtained using these two precursor ions. Alveolar breath ammonia concentrations (which range from 200 to 1750 ppb in these individuals) are compared with those obtained from bag samples of breath from the same individuals.
Keywords: Pulmonary Alveoli; Oxygen; kyslík; Breath Tests; Water; Ammonia; Humans; Dietary Proteins; lidé; dechové testy; amoniak; dietní proteiny; voda; plicní alveoly